Development and internal validation of the PROFIT and POSITIVE prognostic nomograms for patients undergoing VA-ECMO therapy - Shirui Qian; Ping Li; Xiaotong Hou; Nianguo Dong (Scientific Reports)
Abstract This study was aimed at developing and internally validating nomograms for predicting mortality during venoarterial-extracorporeal membrane oxygenation (VA-ECMO) and in-hospital mortality risk in patients treated with VA-ECMO. A total of 7260 patients treated with VA-ECMO from January 2017 to December 2023 were extracted from the Chinese society of extra corporeal life support registry database. The entire cohort was randomly assigned to derivation and validation cohorts at a ratio of 2:1. Multivariable Cox proportional hazards regression was conducted using bootstrapping with the likelihood ratio test and Akaike information criterion. Approximately 24% of patients died during VA-ECMO assistance, and 51% died in the hospital. The nomogram PROFIT was constructed with ten pre- and immediately post-ECMO parameters: age, body mass index (BMI), intra-aortic balloon pump before VA-ECMO, history of cardiac arrest, worst mean arterial pressure (MAP), potential of hydrogen (pH) and serum lactate levels before VA-ECMO, site of ECMO installation, peripheral cannulation and distal perfusion. Additionally, nomogram POSITIVE was also established with ten parameters: age, sex, BMI, history of cardiac arrest, MAP, pH, and serum lactate levels before VA-ECMO support, the occurrence of cardiac arrest before VA-ECMO, type of sedation and prior continuous renal replacement therapy. The area under the receiver operating characteristics (AUC) of the nomogram PROFIT (0.72 [95% CI 0.70–0.74]) and POSITIVE (0.71 [95% CI 0.68–0.73]) outperformed the SAVE score, which indicated that the nomograms were capable of effectively identifying patients with a high risk of mortality. Both nomograms demonstrated outstanding discrimination and calibration in derivation and validation cohorts. In patients treated with VA-ECMO, the nomogram PROFIT may serve as a valuable tool for predicting mortality during VA-ECMO assistance, and the nomogram POSITIVE can predict in-hospital mortality with high reliability. However, these tools still require external validation in other patient populations requiring VA-ECMO support.